The measurement of environmental and resource values : theory and methods - Freeman, A. Myrick, 1936-; Herriges, Joseph A., 1956-; Kling, Catherine L. (New York : RFF Press, 2014)
'The first edition of this important work was the winner of the 2002 Publication of Enduring Quality award by the Association of Environmental and Resource Economists. The continuing premise for the book is that estimates of the economic values of environmental and natural resource services are essential for effective policy-making. As previous editions, the third edition, which includes two additional co-authors, presents a comprehensive treatment of the theory and methods involved in estimating environmental benefits. Researchers, policy-makers, and practitioners will welcome the work as an up-to-date reference on recent developments. Students will gain a better understanding of the contribution that economics as a discipline can make to decisions concerning pollution control and human health, recreation, environmental amenities, and other critical issues concerning the way we use and interact with environmental and natural resource systems. To reflect recent progress in both the theory and practice of non-market valuation, the third edition includes more details on empirical approaches to measurement, expanded discussion of the reasons for divergence between'willingness to pay' and'willingness to accept compensation,' and increased coverage of econometric issues encountered in estimation. In keeping with its cutting edge orientation, it also includes more discussion of survey design, equilibrium sorting models, and the implications of behavioral economics for welfare measurements and benefit cost analysis'--
'The first edition of this important work was the winner of the 2002 Publication of Enduring Quality award by the Association of Environmental and Resource Economists. The continuing premise for the book is that estimates of the economic values of environmental and natural resource services are essential for effective policy-making. As previous editions, the third edition, which includes two additional co-authors, presents a comprehensive treatment of the theory and methods involved in estimating environmental benefits'--
1. Resource evaluation and public policy -- 2. Measuring values, benefits, and costs : an overview -- 3. Welfare measures : definitions and concepts -- 4. Welfare measures : theoretical basis for empirical assessment -- 5. Valuing changes in risk -- 6. Aggregation of values across time -- 7. Valuing longevity and health -- 8. Environmental quality as a factor input -- 9. Recreation demand -- 10. Property value models -- 11. Hedonic wage models -- 12. Stated preference methods for valuation -- 13. Additional topics -- 14. Conclusions : state of the art and research needs.
Keywords: Environmental policy -- Cost effectiveness; Environmental policy -- Evaluation